Trinidad and Tobago Equal Opportunity (No.2) Bill, 1998 - Trinidad and Tobago (My University, 1998)
An Act to prohibit certain kinds of discrimination, to promote equality of opportunity between persons of different status, to establish an Equal Opportunity Commission and an Equal Opportunity Tribunal and for maters connected therewith.
Note: Legal Supplement Part C to the "Trinidad and Tobago Gazette". Vol 37. No.219, 23rd November, 1998. Forth Session of the Fifth Parliament Republic of Trinidad and Tobago.
Keywords: Equal opportunity